Cell anatomy study of chemotherapy effect on skeletal myofibers diameter - صارم, بسام; عبد الجواد قبيلي ,; علي داود , (Latakia University Journal -Medical Sciences Series, 2023)
The Study involved tow randomized groups with advanced NonHodgkin's Lymphoma NHL (B-cells) Stage III. The control group included 21 patients before chemotherapy while the cases (oppose) one's included 30 patients after chemotherapy with CHOP-R protocol is finished (cyclophosphamide, doxorubicin, vincristine and prednisone) in 6 cycles 3 weeks apart. Skeletal muscle biopsies performed using needle biopsy. Scanning electron microscope study performed at the Atomic Energy Agency. Results revealed normal values for skeletal muscle fibers in control group while in case group 40% of patients after chemotherapy showed an important decrease in myofibers diameter.